A novel method for real time quantitative RT-PCR. - Gibson, U E; Heid, C A; Williams, P M

(untitled) (Genome Research, 1996)
A novel approach to quantitative reverse transcriptase polymerase chain reaction (QC RT-PCR) using real time detection and the 5' nuclease assay has been developed. Cystic fibrosis transmembrane transductance regulator (CFTR) target mRNA is reverse transcribed, amplified, detected, and quantitated in real time. A fluorogenic probe was designed to detect the CFTR amplicon. Relative increase in 6-carboxy-fluorescein reporter fluorescent emission is monitored during PCR amplification using an analytical thermal cycler. An internal control template containing the same primer sequences as the CFTR amplicon, but a different internal sequence, has been designed as a control. An internal control probe with a reporter fluorescent dye tetrachloro-6-carboxy-fluorescein was designed to hybridize to the internal control amplicon. The internal control template is placed in each reaction tube and is used for quantitative analysis of the CFTR mRNA. This method provides a convenient and high-throughput format for QC RT-PCR.